2018
DOI: 10.14260/jemds/2018/63
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bacteriological Profile and Antibiotic Sensitivity Pattern in Samples Received From Patients Attending Tertiary Care Hospital in Mumbai

Abstract: BACKGROUND Bacterial infections are important cause of morbidity and mortality among patients and antimicrobial resistance is a significant growing global threat. In this era of multidrug resistance, it is mandatory to know the bacteriological profile and antimicrobial sensitivity pattern of one's own institute. Hence, the following study was conducted to document the common bacteria isolated from various clinical specimens from patients of our institute and describe their antibiotic susceptibility. MATERIALS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In support of our results, Barai et al, 2021 [18] also reported 30.2% wound/pus swab from the samples collected between the 2001 to 2021. Whereas study of Jangla and Naidu (2018) [17] reported only 5.5% of wound swab and pus samples. The results of the prevalence analysis among the bacterial and fungal isolates indicates the incredible prevalence of the Staphyloccus auerus (306), followed by the Escherichia coli ( 137 The study of Biswas et al, 2021 [19] on prevalence of methicillin resistant Staphylococcus aureus in pus samples in a tertiary care hospital of eastern India reported the 4.6% to 54.4% prevalence of methicillin resistant Staphylococcus aureus.…”
Section: Resultsmentioning
confidence: 92%
“…In support of our results, Barai et al, 2021 [18] also reported 30.2% wound/pus swab from the samples collected between the 2001 to 2021. Whereas study of Jangla and Naidu (2018) [17] reported only 5.5% of wound swab and pus samples. The results of the prevalence analysis among the bacterial and fungal isolates indicates the incredible prevalence of the Staphyloccus auerus (306), followed by the Escherichia coli ( 137 The study of Biswas et al, 2021 [19] on prevalence of methicillin resistant Staphylococcus aureus in pus samples in a tertiary care hospital of eastern India reported the 4.6% to 54.4% prevalence of methicillin resistant Staphylococcus aureus.…”
Section: Resultsmentioning
confidence: 92%